Students’ Mathematical Reasoning Skills in Solving Mathematical Problems - Christine Iriane Gultom; Triyanto; Dewi Retno Sari Saputro (Jurnal Pendidikan Indonesia, 2022)
Mathematical material will be easily understood through reasoning and that reasoning skills can be trained through mathematics learning. However, there are still many students who do not have good reasoning skills. This study aims to analyses the mathematical reasoning skills of class XI students of Senior High School on trigonometry in solving mathematical problems. This research is a qualitative descriptive study. The participants of this study were 2 students, namely student 1 (S1) and student 2 (S2) who were selected by purposive sampling. The instruments used to explore this mathematical reasoning skill were written tests and interviews. Triangulation method was employed to validate the data. The results showed that S1 was able to meet the reasoning indicator in proposing conjectures, predicting the answers and the solution process, performing mathematical manipulation and concluding sentences at the end of a completion. S2 was able to meet the reasoning indicator in proposing conjectures and predicting the answers and the solution process. However, S2 was less capable in performing mathematical manipulation and less capable concluding sentences at the end of a completion.